2022
DOI: 10.3390/life12020173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 52-Week Single Inhaler Device Triple Therapy versus Dual Therapy on the Mortality of COPD Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: There are more single inhaler device triple therapy available for COPD patients now. However, the effect of long-term triple therapy fixed dose combination (FDC) on mortality remains unclear. This study aimed to evaluate the impact of one-year single inhaler device triple therapy, including long-acting β2-agonists (LABAs), long-acting muscarinic receptor antagonists (LAMAs), and inhaled corticosteroids (ICSs), with dual therapies, comprised of either LABA/LAMA or ICS/LABA, on the mortality of patients with COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Although the therapeutic effects of ICS containing therapies such as ICS/LAMA/LABA and ICS/LABA increase with the increase of blood eosinophil count, the exact mechanism of this benefit in patients with COPD is still unclear [15].A RCT was conducted to explore theefficacy of single inhalation,triple inhalation and double inhalation therapy for 52 weeks.The primary end point was all-cause mortality.They found that the risk of death was apparently lower in the triple inhalation FDC group than in the double inhalation therapy group(p=0.006),but in mortality,there was no apparent difference between the triple inhalation FDC and double inhalation therapy treatment groups(p=0.66).Besides,patients treated with triple inhalation FDC had less moderate or severe exacerbation than those in the dual treatment group.However, the risk of pneumonia of the triple inhalation FDC group is higher than the double inhalation therapy group [16].…”
Section: Triple Therapy Of Copdmentioning
confidence: 84%
“…Although the therapeutic effects of ICS containing therapies such as ICS/LAMA/LABA and ICS/LABA increase with the increase of blood eosinophil count, the exact mechanism of this benefit in patients with COPD is still unclear [15].A RCT was conducted to explore theefficacy of single inhalation,triple inhalation and double inhalation therapy for 52 weeks.The primary end point was all-cause mortality.They found that the risk of death was apparently lower in the triple inhalation FDC group than in the double inhalation therapy group(p=0.006),but in mortality,there was no apparent difference between the triple inhalation FDC and double inhalation therapy treatment groups(p=0.66).Besides,patients treated with triple inhalation FDC had less moderate or severe exacerbation than those in the dual treatment group.However, the risk of pneumonia of the triple inhalation FDC group is higher than the double inhalation therapy group [16].…”
Section: Triple Therapy Of Copdmentioning
confidence: 84%
“…), conference abstract, article comment, protocols, and ineligible comparator or outcomes ( Supplemental File 3 ). Finally, we judged 18 SRs 22 39 as eligible for inclusion in this overview ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Triple therapy also demonstrated a significant impact on mortality and frequency of moderate or severe exacerbations compared with LABA/LAMA. 2,33,34 Our observations showed that patients treated with triple therapy remained on triple therapy throughout the study, whereas patient prescribed ICS/LABA were often stepped up to triple therapy. In spite of the recommendation for ICS treatment only in patients that experience exacerbations, 2 in our real life study we observed that the prevalence of ICS prescription in clinical practice reaches 50% of the patients enrolled, suggesting the possibility of overtreatment or inadequate disease control despite maximized bronchodilation in a proportion of patients.…”
mentioning
confidence: 79%